Electrochemiluminescence and Photoluminescence of Carbon Quantum Dots Controlled by Aggregation-Induced Emission, Aggregation-Caused Quenching, and Interfacial Reactions - Adsetts, Jonathan Ralph (Langmuir : the ACS journal of surfaces and colloids, 2020)
Carbon quantum dots (CQDs) show promise in optoelectronics as a light emitter due to simple synthesis, biocompatibility and strong tunable light emissions. However, CQDs commonly suffer from aggregation caused quenching (ACQ), inhibiting the full potential of these light emitters. Studies into different ideal light emitters have shown enhancements when converting common ACQ effects to aggregation induced emission (AIE) effects. We report CQD synthesis using citric acid and high/low thiourea concentrations, or sample 2/1. These two CQDs exhibited AIE and ACQ PL effects, respectively. CQD characterizations and photoluminescence interrogations of CQD films and solutions revealed that these unique emission mechanisms likely arose from different S incorporations into the CQDs. Furthermore, it was discovered that sample 2 emitted electrochemiluminescence (ECL) more intensely than sample 1 in a homogenous solution with S2O82- as a coreactant, due to aggregation and interactions of CQD species in solution. Very interestingly, sample 1's CQD film|S2O82- system achieved an ECL efficiency of 26% and emitted roughly 26 times more efficiently than sample 2 in the same conditions. Predominant interfacial reactions and surface state emission produced intense white light with a correlated color temperature of 2000 K. Spooling ECL spectroscopy was utilized to investigate emission mechanisms. Sample 2's CQD film|TPrA system had four times higher ECL intensity than that of sample 1, most likely due to π-cation interactions leading to a strong CQD•+ stability, thereby, enhancing ECL. It is anticipated that ECL enhancement of CQD films or solutions by means of AIE will lead to wide CQD optoelectronic applications